PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Libbaskara, Wahyu Putra; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2022)
Humans must adapt to a pandemic, but on the other hand the wheels of the economy must still run so that the condition of a country can remains stable and maintained. Employee performance during a pandemic is one of the main things that must be considered by companies, because whether employees are productive or not will affect company productivity, and company productivity will play a role in a country's economic growth, especially during this period. the Covid-19 pandemic. The purpose of this quantitative research is to identify partial effects of job stress and work motivation on the performance of employees of PT. Bank Rakyat Indonesia (Persero) Tbk. branch office of Malang Kawi During the Covid-19 Pandemic. Here multiple linear regression analysis was performed on data harvested from offline questionnaires distributed to 100 employees of the bank. Validity and reliability tests were conducted to each research variable. The results of the calculation in SPSS version 25 have led to findings that job stress (X1) negatively and significantly affects employee performance (Y), and that work motivation (X2) positively and significantly influences employee performance (Y).